Communication Style Analysis of @icha_atazen in Promoting Fibermi Products Through Instagram Stories - Ayu Andira; Eka. M. Taufani; Agus Slamet Nugroho; Mila Wahyuni (Journal of Communication, 2026)
The development of social media, particularly Instagram, has created new opportunities for effective product promotion through interactive features such as Instagram Story, which enables users to share engaging, personal, and audience-centered content. The Instagram account @icha_atazen utilizes this feature to promote Fibermi products by highlighting personal experiences, consumer testimonials, and interactive communication with followers. This study aims to identify and analyze the communication styles used by @icha_atazen in promoting Fibermi products through Instagram Story and to understand how these styles are conveyed to the audience. Data were collected through observation and documentation of relevant Instagram Story posts and analyzed by categorizing content based on these style indicators. The results show that open style appears through honest personal sharing, dominant style through firm instructions, friendly style through supportive interaction, and relaxed style through casual language. In conclusion, these styles are applied contextually, forming varied communication; future studies should explore other platforms or influencers.